System z bazą wiedzy w rachunkowości zarządczej - Iwasieczko, Beata (The Knowledge Based System in Managerial Accounting, 2005)
The principal objective of this article is to answer the question concerning the main factors which determine the effective communication in the knowledge based system in the managerial accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 277-283